Relationship between Nature of Science Tenets and High School Students’ Acceptance of Evolutionary Theory in Cameroon - Dr. Lawrence Ntam Nchia; Pr. Judith Njomgang Ngansop; Dr. Ernestine Tani Wirngo; Bouni, Pr. Ayina (American Journal of Education and Practice, 2024)
Purpose: Low levels of evolution acceptance have been reported among students in several articles using the Measure of Acceptance of the Theory of Evolution (MATE) instruments. Amongst possible causes listed in literature are students’’ religious, sociocultural background and educational approach used in teaching. Some studies have revealed that students who have a better understanding of the nature of science (NOS) are more likely to accept evolution, but the relationship between NOS and MATE has not been scientifically established. This article seeks to establish the relationship between NOS and MATE. Materials and Methods: A cross sectional survey was done using Structural Equation Modelling (SEM) techniques to investigate the extent to which NOS tenets enhance biology students’ acceptance of evolution using 482 purposeful and convenient sample size. The validity and reliability of the NOS and MATE instruments were investigated and standardised using Exploratory and Confirmatory Factor Analysis. Thereafter, a hypothesised SEM model was conceptualised and tested. Findings: The model provided a reasonable good overall fit. Only understanding of three NOS tenets namely: The empirical nature of science; use of observation and inferences in science; and the nature of scientific laws and theories has a strong positive statistically significant direct effect on acceptance of evolution. The tentativeness, subjectivity and objectivity of science, and the use of creativity and imagination in science did not significantly enhance acceptance of evolution. Implications to Theory, Practice and Policy: This can serve as a candidate theory for further investigation. It could have implication in the development of didactic strategies to overcome misconceptions in evolution.